2020
DOI: 10.1111/all.14471
|View full text |Cite
|
Sign up to set email alerts
|

ARIA‐EAACI statement on asthma and COVID‐19 (June 2, 2020)

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
107
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 72 publications
(115 citation statements)
references
References 19 publications
3
107
0
5
Order By: Relevance
“…All of the participants reported that they took precautions for infection prevention and control at their hospitals. Participants were using national and international societies' guidelines and online services such as those of the TNSACI, the European Academy of Allergy and Clinical Immunology (EAACI), the World Allergy Organization (WAO), and the Global Initiative for Asthma (GINA) as resources for COVID-19 [ 1 , 2 , 3 , 4 , 5 ]. Telemedicine was used for the management of asthma (73%), allergic rhinitis (53%), atopic dermatitis (51%), chronic urticaria/angioedema (59%), drug hypersensitivity (45%), food allergy (48%), venom allergy (30%), anaphylaxis (22%), and hereditary angioedema (28%).…”
Section: Resultsmentioning
confidence: 99%
“…All of the participants reported that they took precautions for infection prevention and control at their hospitals. Participants were using national and international societies' guidelines and online services such as those of the TNSACI, the European Academy of Allergy and Clinical Immunology (EAACI), the World Allergy Organization (WAO), and the Global Initiative for Asthma (GINA) as resources for COVID-19 [ 1 , 2 , 3 , 4 , 5 ]. Telemedicine was used for the management of asthma (73%), allergic rhinitis (53%), atopic dermatitis (51%), chronic urticaria/angioedema (59%), drug hypersensitivity (45%), food allergy (48%), venom allergy (30%), anaphylaxis (22%), and hereditary angioedema (28%).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, SARS-CoV-2 can easily reach the lower airways by binding to ACE2 receptors in the bronchi cells and type II alveolar cells, and may aggravate asthma. However, the ARIA-EAACI statement has reported that asthma does not seem to be a risk factor for severe COVID-19 (7).…”
Section: Coronaviruses and Asthma Exacerbationsmentioning
confidence: 99%
“…The Centers for Disease Control and Prevention (CDC) has stated that subjects with moderate to severe asthma may have an increased risk for COVID-19 and the infection may lead to an asthma attack, pneumonia, or acute respiratory disease (6). However, the ARIA-EAACI statement on Asthma and COVID-19 has reported that asthma does not seem to be a risk factor for severe COVID-19 (7). Only asthma patients using oral corticosteroids were defined as a risky group for COVID-19 or severe asthma flare-ups (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sputum cells among patients with asthma may give a risk for COVID-19 morbidity [15]. The prevalence of COVID-19 among asthmatic patient was 9% [16]. Yet, there is no pooled result of the COVID-19 burden, admission and outcome among asthmatic patients in Africa.…”
Section: Introductionmentioning
confidence: 99%